The German manufacturing sector is a granular economy - Joachim Wagner (Institute for the Study of Labor (IZA), 2011)
Using the approach suggested by Gabaix (Econometrica 2011) this paper demonstrates that idiosyncratic shocks in the largest firms are important for an understanding of aggregate volatility in German manufacturing industries. The implications of this finding for theoretical and empirical research and for economic policy are discussed.
urn:nbn:de:101:1-201111303472
Keywords: E32; 330; power law; idiosyncratic shocks; granular residual; Germany; Unternehmenserfolg; Großunternehmen; Schock; Produktivität; Verarbeitendes Gewerbe; Branchenkonjunktur; Konjunktur; Makroökonomischer Einfluss; Schätzung; Deutschland